2004
DOI: 10.1111/j.1083-4389.2004.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection and Immune Thrombocytopenic Purpura: an Update

Abstract: Data are accumulating on the association between Helicobacter pylori infection and idiopathic thrombocytopenic purpura (ITP) and the significant increase in platelet count after bacterial eradication. The aim of this review was to consider the studies so far published on H. pylori infection and ITP in order to evaluate a possible correlation between these two conditions. A review of the literature showed that 278 out of the 482 ITP patients investigated (58%) were positive for H. pylori infection and that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 38 publications
1
56
0
1
Order By: Relevance
“…*Nonresponders to eradication treatment. infection in our series is not higher than that (58%) in the general population of the area of Modena province, 36 or that (67%) in healthy Italian blood donors aged 50 years or older, 37 in keeping with the data from the other countries, where the prevalence of infection in patients with ITP is similar or lower than that of the general population of the same area, 6,10,13,38,39 with rare exceptions. 15,40 In our study, we observed a platelet improvement in 68% of patients with eradicated infection (60.5% of patients infected; 30.6% of total patients with ITP); in about 1500 patients so far reported in the literature, including the 3 US and Spanish cohorts with the lowest responses, the rate of response was about 53%.…”
Section: Discussionsupporting
confidence: 81%
“…*Nonresponders to eradication treatment. infection in our series is not higher than that (58%) in the general population of the area of Modena province, 36 or that (67%) in healthy Italian blood donors aged 50 years or older, 37 in keeping with the data from the other countries, where the prevalence of infection in patients with ITP is similar or lower than that of the general population of the same area, 6,10,13,38,39 with rare exceptions. 15,40 In our study, we observed a platelet improvement in 68% of patients with eradicated infection (60.5% of patients infected; 30.6% of total patients with ITP); in about 1500 patients so far reported in the literature, including the 3 US and Spanish cohorts with the lowest responses, the rate of response was about 53%.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with these observations, sepsis patients often experience thrombocytopenia, indicating that platelets may participate in responding to infections (14,24). Most studies of platelet-bacterium interactions have included platelet aggregation assays and measurement of the expression of activation markers.…”
mentioning
confidence: 90%
“…Indeed, Annibale et al [5] have reported iron deficiency anemia improved after eradication of HP infection. However, studies are also available that reporting increase in platelet count after eradication of HP in patients with immune thrombocytopenic purpura [6,7]. There was a little study that investigating the relationship between whole blood parameters and HP infection.…”
Section: Introductionmentioning
confidence: 99%